2019
DOI: 10.3390/ijms20092190
|View full text |Cite
|
Sign up to set email alerts
|

Silybin-Induced Apoptosis Occurs in Parallel to the Increase of Ceramides Synthesis and miRNAs Secretion in Human Hepatocarcinoma Cells

Abstract: Silybin is a flavonolignan extracted from Silybum marianum (milk thistle) with hepatoprotective, antioxidant, and anti-inflammatory activity. Several studies have shown that silybin is highly effective to prevent and treat different types of cancer and that its antitumor mechanisms involve the arrest of the cell cycle and/or apoptosis. An MTT assay was performed to study cell viability, lipid peroxidation, extracellular NO production, and scavenger enzyme activity were studied by Thiobarbituric Acid-Reactive S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Previous studies found that SIL inhibits ERK1/2 signaling, which indicates that the ERK1/2 signaling pathway may play as an upstream regulator that modulates the SIL-induced Bim signaling pathway. In addition, the effect of SIL on the prohibition of angiogenesis in hepatic cancers is associated with reduced secretion of vascular endothelial growth factor, CD34, and metalloproteinase-2 in a dose dependent manner (Li and Wang, 2016;Zappavigna et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that SIL inhibits ERK1/2 signaling, which indicates that the ERK1/2 signaling pathway may play as an upstream regulator that modulates the SIL-induced Bim signaling pathway. In addition, the effect of SIL on the prohibition of angiogenesis in hepatic cancers is associated with reduced secretion of vascular endothelial growth factor, CD34, and metalloproteinase-2 in a dose dependent manner (Li and Wang, 2016;Zappavigna et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Silymarin (Sm) and silibinin (Sb) are investigated to exert strong antineoplastic effects in both in vitro and in vivo models of cancer, including cancers of the prostate, bladder, skin, colon, lung, breast, and kidney [35][36][37][38][39][40][41]. During Sm and Sb treatment, several mechanisms have been applied, such as DNA repair, cell cycle arrest, inhibition of growth and pro-liferation in addition to antiangiogenic effects, and blockage of invasion and metastasis [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have proved that the abnormal expression of miRs is related to the development of a series of cancers, including HCC [ 29 , 30 ]. Also, circRNAs take part in the advancement of a range of tumors by sponging miRs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%